The Information Research Department, unattributable propaganda, and Northern Ireland: promising salvation but ending in failure? - Cormac, Rory (Oxford University Press, 2016)
This article examines the role of the IRD (Information Research Department) in Northern Ireland during the first half of the 1970s. After discussing British conceptualisations of propaganda, it offers a detailed account of IRD activity, including how a Foreign Office department came to be involved on British soil; how IRD propaganda fitted into the broader apparatus in Northern Ireland; the activity in which the IRD was engaged – both in Northern Ireland and beyond; and some of the challenges faced which limited the campaign’s effectiveness. It argues that the IRD’s role was driven from the very top of government and came against a context of cuts, a deteriorating security situation in Northern Ireland, and a tradition of domestic propaganda in the UK. IRD activity pressed four key themes: exploiting divisions within the IRA; undermining the IRA’s credibility amongst the population; linking the IRA to international terrorism; and portraying the IRA as communist.